FORUM EKSPERTÓWThe New EuroSCORE Project - Nashef, Samer A.M. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
on behalf of the EuroSCORE Project team